1995
DOI: 10.1111/j.1751-0813.1995.tb06190.x
|View full text |Cite
|
Sign up to set email alerts
|

Settling of insecticide from dip wash mixed with dam water and zinc sulphate and used to control sheep lice (Bovicola ovis)

Abstract: Insecticidal dipping fluid emulsions, mixed in vitro in dam water containing suspended clay particles and 1% w/v zinc sulphate, were analysed to determine rates of settling of diazinon, cyhalothrin and cypermethrin. Fifteen minutes after mixing, the concentration of the insecticides 5 cm below the surface had declined by 72.5%, 72.8% and 89.4%, respectively. On remixing, the concentration of insecticide in suspension was close to or greater than the initial concentration. In 2 trials, lice were eradicated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The reduction was significant for zinc sulphate concentrations between 0.2% and 1.5%, which covers the range usually used by farmers to prevent dermatophilosis. 6,7 The in-vitro results indicated that increasing the concentration of zinc sulphate from 0.5% to 1.5% made little difference to the wetting ability of the dip wash. In both the field and in-vitro experiments, treatments with higher concentrations of zinc sulphate were not consistently those with poorer wetting.…”
Section: Fleece Wetting After Dippingmentioning
confidence: 95%
See 4 more Smart Citations
“…The reduction was significant for zinc sulphate concentrations between 0.2% and 1.5%, which covers the range usually used by farmers to prevent dermatophilosis. 6,7 The in-vitro results indicated that increasing the concentration of zinc sulphate from 0.5% to 1.5% made little difference to the wetting ability of the dip wash. In both the field and in-vitro experiments, treatments with higher concentrations of zinc sulphate were not consistently those with poorer wetting.…”
Section: Fleece Wetting After Dippingmentioning
confidence: 95%
“…Downing 5 published some concerns about the effect of adding zinc sulphate to dip wash, a common practice for the purpose of minimising the spread of dermatophilosis. 6,7 He reported flocculation of the dip wash, which was made using dam water, and a subsequent decrease in the diazinon concentration in the supernatant. Similar findings were reported by Morcombe et al 7 with diazinon, cypermethrin and cyhalothrin.…”
Section: Ddtmentioning
confidence: 99%
See 3 more Smart Citations